Genomes of the Golden Horde elites and their implications for the rulers of the Mongol Empire - Ayken Askapuli; Hideaki Kanzawa-Kiriyama; Tsuneo Kakuda; Aibar Kassenali; Syrym Yessen; Uli Schamiloglu; Steven J. Schrodi; John Hawks; Naruya Saitou (Proceedings of the National Academy of Sciences, 2026)
The Golden Horde, the northwestern extension of the Mongol Empire ruled by Genghis Khan’s descendants, holds a pivotal place in the history of Central Eurasia and Eastern Europe. Consequently, understanding the genetic legacy of Genghis Khan and his lineage has long been of both academic and public interest, especially concerning the hypothesized association of his Y-chromosome with haplogroup C3*. Here, we present ancient DNA data from four archaeological individuals—three males and one female—from medieval elite mausoleums of the Golden Horde in the Ulitau region of Kazakstan. Our genomic analyses reveal that the three male individuals are paternally related and share the Y-chromosome haplogroup C3*, confirming the association between the Y-chromosome haplogroup C3* and the Mongol Empire, supporting the long-standing hypothesis about the genetic legacy of Mongols. Additionally, our findings demonstrate that the Golden Horde elites primarily derive their genomes from Ancient Northeast Asians (ANA), with an additional ancestral component from either Ancient North Eurasians (ANE) or a Berel Scythian related population, e.g., the Kipchaks. Archaeological evidence, in turn, sheds light on a medieval population undergoing religious and cultural transition, offering insights into the societal changes experienced by Mongolian conquerors. Furthermore, through constructing an Identity by Descent (IBD) network, we successfully identify medieval relatives of these individuals on the Mongolian Plateau, linking genetic data to broader population dynamics. In essence, this study provides ancient DNA evidence that advances our understanding of the genetic background of the Mongolian elites and the population dynamics in Central Eurasia.